Elaboração, contratação e execução de obras públicas - Lima, Andressa Ellen Silva de (2019)
The execution of public works requires from the administrations a great planning of the bidding phases. However, in order for the delivered works to be performed satisfactorily, qualified professionals, knowledge of current legislation, projects and accurate complementary documents are required. The monograph developed aims to advise professionals involved in the process of contracting public works, through the explanation of concepts and definitions of issues related to the theme. As methodology is adopted a literary research based on legislations, books, monographs and manuals prepared by normative bodies, later we analyze four municipal works completed for extraction of common data arising in various phases of the bidding process. The elaboration of this case study results in a proposal for a management tool, composed of different and orderly steps of procedures that should be employed throughout the project phases, contracting, execution of the object until its use by the population. It is concluded that the main problems encountered during the execution of a work originate from the incomplete elaboration of the initial phases, resulting in inconsistent projects, contractual additives, works without qualities, paralyzed or unfinished.